Implementation of Analytical Hierarchy Process (AHP) Method In Determining Expedition Services at the Market Place - Purwanto, Heru; Ishak, Riswandi (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
The delivery of goods is an important part, where the seller's efforts in sending the order package reach the consumer and become a satisfaction for consumers to be able to reason again.  Decision-making   is often faced with a number of confusing choices, especially in the selection of expedition services.  The selection of acquisition services is the main point in supporting business processes. The purpose of this study provides more important criteria for determining alternative expedition services.  This research used the Analytical Hierarchy Process (AHP) Method. Pairwise comparison questionnaires are given to obtain the degree of importance of the criteria. Price Criteria are the highest criteria in this study compared to location criteria, services and responses. Meanwhile, the response criteria that have sub criteria for claiming goods are more important than the sub criteria for ordering and tracking goods while the service criteria where in the sub criteria for losing goods are a  more important condition than damage to goods, speed of delivery criteria . These criteria are used to determine the best choice of expedition services so that from the calculation results of the three alternatives obtained the top ranking with a value of 0.546933. Keywords : AHP,  Expedition Services, Market Place